Report of Health Behavior Modification Among Latinos Diagnosed With Multiple Cardiovascular Risk Factors. Issue 1 (January 2020) - Gonzalez, Tailisha M.; Katic, Bozena J.; Torres-Págán, Leonell; Divney, Anna; Echeverria, Sandra E.
Abstract : Introduction: Hypertension, hypercholesterolemia, and type II diabetes are leading cardiovascular risk factors in the United States, and Latinos are disproportionately burdened by these chronic health conditions. The extent to which Latinos overall and by language spoken at home report health behavior modification following diagnosis is poorly understood. Methods: Our inclusion criteria included participants sampled in the 2011–2016 waves of the National Health and Nutrition Examination Survey who self-identified as Latinos, were 20 years of age or above, and reported a diagnosis of hypertension, hypercholesterolemia or diabetes (N=2027). We examined associations between the language spoken at home and report of adoption of 3 recommended health behaviors in the past year: weight loss, leisure-time physical activity (LTPA) and smoking cessation. Separate log-binomial models were fit to estimate prevalence ratios (PRs) for each health behavior. Results: Approximately one third (28%) of study participants had been diagnosed with diabetes and more than half reported a diagnosis of hypercholesterolemia (65%) or hypertension (60%). Most Latinos met the highest levels of smoking cessation criteria (82%), whereas less than a third met LTPA recommendations (29%) or attempted weight loss (24%) in the past year. Fully adjusted outcome specific models showed that exclusively speaking English at home was associated with a higher probability of reporting weight loss attempt and LTPA compared with Spanish only speakers, although only LTPA was statistically significant [weight loss PR: 1.23, 95% confidence interval (CI): 0.92, 1.65; LTPA PR: 1.74; 95% CI: 1.37, 2.20; smoking cessation PR: 0.93, 95% CI: 0.86, 1.01]. Conclusions: Our findings provide new evidence on patterns of behavioral modification in a population-based sample of Latinos diagnosed with chronic health conditions. Findings suggest the need to promote language and culturally relevant initiatives to increase the adoption of health-enhancing behaviors and improve chronic disease management among Spanish-speaking Latinos.